Barriers and motivators to pre-exposure prophylaxis uptake among Black and Latina transgender women in Los Angeles: perspectives of current PrEP users. Issue 2 (1st February 2021) - Nieto, Omar; Fehrenbacher, Anne E.; Cabral, Alejandra; Landrian, Amanda; Brooks, Ronald A.
ABSTRACT: The purpose of this qualitative study was to identify barriers and motivators to PrEP uptake from the perspective of Black and Latina transgender women (TW) who are currently using PrEP to suggest intervention and outreach activities to increase PrEP uptake in this population. The Information-Motivation-Behavioral Skills Model guided the development of the semi-structured interview guide. A thematic analysis approach was used to analyze the data. Perceived barriers to PrEP uptake included structural and logistic barriers, language and cultural barriers to medical engagement, lack of transgender competent or gender-affirming care, and prioritizing hormone therapy over the use of PrEP. To increase PrEP uptake among BLTW, participants recommended disseminating PrEP information through a variety of methods, highlighting relationship and sexual health benefits of using PrEP, and developing effective patient-provider communication. Our findings highlight several ways to promote PrEP among BLTW. PrEP promotion should be integrated into gender-affirming care and supported by peer education and navigation services that reach BLTW in both clinic and community settings.